Bioinspired hyperbranched protein adhesive based on boronic acid-functionalized cellulose nanofibril and water-soluble polyester. (15th August 2021) - Li, Kuang; Jin, Shicun; Wei, Yanqiang; Li, Xiaona; Li, Jiongjiong; Shi, Sheldon Q.; Li, Jianzhang
A bstract: The development of high-performance and sustainable bio-adhesive materials has attracted significant research attention in recent years. However, producing high-performance biopolymer materials with desirable mechanical and antibacterial properties remains a challenge. Herein, a mussel-mimetic strategy is reported to fabricate a soy protein (SP)-based composite film via aqueous co-assembly of 3-aminophenylboronic acid-functionalized cellulose nanofibril (AB@CNF) and hyperbranched polyester (HPE). The water-soluble HPE with numerous hydroxyl end groups was synthesized by using a facile and green method. Through enhanced dynamic covalent interactions and intermolecular sacrificial hydrogen bonds, the incorporated AB@CNF hybrids with conjugated cis -diols strongly interact and entangle with biopolymer chains in the hyperbranched network. As a result of multiple synergistic cross-linking, the toughness and strength of the SP/HPE/AB@CNF film increase by 574% and 346% to 10.05 MJ/m 3 and 14.23 MPa, respectively. Additionally, the film offers excellent antibacterial activity, flame retardance, and thermal stability. This sustainable approach should open new avenues for the design and development of biomimetic plant-derived functional materials in biomass adhesive and active packaging. Graphical abstract: Image 1 Highlights: Protein-based adhesive is fabricated via mussel-inspired interface engineering. Cellulose nanofibril is functionalized by 3-aminophenylboronic acid. Water-soluble hyperbranched polyester is synthesized by a green one-pot method. The toughness and strength of composite simultaneously increase by 574% and 346%. The nanocomposite offers excellent antibacterial activity and flame retardance.